Childhood and the evolution of higher-effort teaching. (2015) - Nielsen, Mark; Shipton, Ceri
Abstract: Kline presents an excellent synthesis of teaching theory and research, with cogent arguments regarding its prevalence. In this, she claims that "active teaching" is human specific, and presents tangible reasons why. But in doing so, she overlooks a critical aspect of the human condition that may have arisen only recently in our evolutionary history: Childhood as a life stage.